Studi Literatur Pengaruh Kinerja Keuangan Daerah Terhadap Pertumbuhan Ekonomi Dan Dampaknya Terhadap Tingkat Pengangguran Serta Pelaku Wirausaha Di Kabupaten Lombok Timur Sebelum Covid 19. - Rachman, Dedy Febry; Amri, Syaiful (Universitas Hamzanwadi, 2023)
This study aims to analyze the impact of financial performance on the unemployment rate. This study used a sample consisting of data related to the financial performance of the region, the economic growth of East Lombok district (in percentages), and the unemployment rate Open (dalam persentase). The observation period covered 2010 to 2019. in this study was tested using double linear regression assisted by SPSS. The results of the study show that: H1: The financial performance of the region, represented by the Independence Ratio, is partially not significantly influenced rejected. H2: The regional financial performance, in particular the Efficiency Rate, has no significant simultaneous effect on the rate of unemployment denied. H3: The efficiency ratio does not have a significant influence on the economic growth denied in part. H4: Regional financial performance involving the independence ratio, the effectiveness ratios, the efficiency ratios and economic growth, does not simultaneally have significant impact on the level of unemployed rejection. H5: Regional Financial performance, especially the Independent Ratio is not indirectly significantly affected by the unemployee rate through the Economic Growth denied; H6: The Regional Financial Performance, the Ratio of Effectiveness, has a direct and indirect influence upon the unsignificant level of Unemployment through Accepted Economic growth. H7: Rational efficiency has no indirect effect on economic growth through direct denial